1977
DOI: 10.1093/oxfordjournals.aje.a112370
|View full text |Cite
|
Sign up to set email alerts
|

THE e ANTIGEN AND VERTICAL TRANSMISSION OF HEPATITIS B SURFACE ANTIGEN

Abstract: The relationship of e antigen (eAg) and its antibody (anti-e) to vertical transmission of hepatitis B surface antigen (HBsAg) from chronic asymptomatic HBsAg carrier women to their children was investigated in Taiwan. Sera from 20 of the 62 women studied were positive for eAg (32%); serum from only one woman was positive for anti-e (2%). A total of 85% of the babies born to eAg positive mothers became HBsAg carriers, while only 31% of the babies became carriers when the mother was eAg negative. Maternal e anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
239
1
10

Year Published

1978
1978
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(256 citation statements)
references
References 0 publications
6
239
1
10
Order By: Relevance
“…Early studies suggested a strong correlation between serum HBeAg and high-titer viremia. For instance, it was observed that HBsAg-positive women who were also HBeAg-positive readily transmitted HBV to their newborn, whereas the risk of transmission was much lower if antibodies to HBeAg, rather than HBeAg, were prevalent in the serum [47]. Thus, anti-HBe antibodies appeared to be a Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies suggested a strong correlation between serum HBeAg and high-titer viremia. For instance, it was observed that HBsAg-positive women who were also HBeAg-positive readily transmitted HBV to their newborn, whereas the risk of transmission was much lower if antibodies to HBeAg, rather than HBeAg, were prevalent in the serum [47]. Thus, anti-HBe antibodies appeared to be a Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-HBc is always present at the onset of disease and reaches a high concentration in sera of patients chronically infected with HBV, but these antibodies do not protect. Anti-HBc passively transmitted to newborns from mothers who are chronic carriers of HBV do not protect these babies from HBV infection (Beasley et al, 1977), indicating that these antibodies do not neutralize the virus. Murray et al (1984Murray et al ( , 1987 and Iwarson et al (1985) demonstrated that immunization of chimpanzees with the core protein of HBV provided complete or partial protection from HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Among pregnant women who are HBsAg carriers there is a high rate of transmission of hepatitis B virus to offspring among those who are e-antigen-positive (Okada et al 1976;Beasley et al 1977). Two of the 4 pregnant HBsAg carriers that we investigated were e-antigen-positive and both, unlike the other 2, who were anti-e-positive, transmitted HBsAg to their children.…”
Section: Discussionmentioning
confidence: 97%